A new approach for credit extended mobile phone payment. (1st January 2014) - Gackle, Bennett; Zuo, Yanjun
In this paper, we present a new approach for credit extended mobile phone payment. As an important component of m-commerce, mobile phones have been enabled to conduct micro-purchases for digital contents for a small price. Currently, mobile phone companies have expanded this to purchasing tangible items such as a Coca-Cola or other vending items through a radio frequency identification device chip. This paper will explore the idea to expand beyond micro-purchases and essentially use the mobile phone, the mobile network operator (mobile phone carrier), and an embedded near-field-communication (NFC) chip to make full purchases similar to credit cards. We have developed the business model and a technical framework to support and implement the proposed strategy.